PENYULUHAN GAMSTING (GERAKAN MEMASYARAKATKAN MAKAN IKAN UNTUK MENCEGAH STUNTING) DI PAUD RINJANI DARMA WANITA UNIVERSITAS MATARAM - Yuliana Asri; Septiana Dwiyanti; Alis Mukhlis; Andre Rachmat Scabra; Laily Fitriani Mulyani; Wastu Ayu Diamahesa; Nuri Muahiddah; Muhammad Sumsanto; Lalu Hizbulloh (Universitas Mataram, 2023)
Stunting is a condition of nutritional status in children under five years of age with low height compare to age. The data from the National Nutrition Status Survey (SSGI) of 2022 shows that one out of every five children in Indonesia is stunted. The Movement to Popularize Eating Fish to Prevent Stunting (GAMSTING) is an effort to reduce stunting prevalence in Indonesia. Children, especially those in the pre-school period such as in day care, early childhood education and kindergarten, are an important target in stunting prevention education. This service activity aims to provide education to teachers, parents and students at Kindergarten DW Rinjani University of Mataram about the importance of nutrition fulfillment from an early age to prevent stunting, one of which is by consuming fish. This service uses the counseling method with material on the introduction of types of sea fish and fresh fish, as well as the importance of eating fish for the health and fulfillment of children's nutrition. The second counseling material is the hands-on practice of cooking tuna. Students and parents who attended the activity were enthusiastic in participating in the activity both in material presentation and in tasting the fish dishes from the cooking demonstration. Collaboration among children, parents and teachers at school in introducing and increasing fish consumption is expected to be an important measure to prevent stunting. Diet is very influential on the growth and development of children so that the toddler period is most appropriate for parents to introduce and get used to their children consuming fish.